Application of Time Cost Trade Off Method in Optimizing Time and Cost on Ship Refurbishment Projects KMP Dharma Rucitra 1 and MT Triaksa 17 - Imam Pujo Mulyatno; Hani Niswa Humaida; Wilma Amiruddin; Berlian Arswendo Adietya; Hartono Yudo (International Journal of Marine Engineering Innovation and Research, 2024)
Delays that occur in the KMP Dharma Rucitra 1 ship refurbishment project have an impact on the MT Trikasa 17 ship refurbishment project, so that the project work must be accelerated in order not to exceed the contract. This study aims to overcome the delays that occur by finding the most optimal time acceleration value and the minimum cost. The time cost trade off method is often used in scheduling the repair of two or more ship units simultaneously to optimize project time and cost, so this method is considered to be able to overcome the problems that occur. Based on the repair list and main schedule data, the critical trajectory and productivity values of each job were obtained. The work on the critical trajectory was treated with variations of additional working hours (overtime) and variations of additional workers. The analysis shows that the addition of working hours (overtime) provides effective results, namely the addition of 1 working hour (overtime) with a reduction in time by 12.5% and a cost of Rp. 253,236,000 (4.35% increase). While the addition of labor provides effective results, namely the addition of 4 workers with a 25% reduction in time and costs of Rp. 245,140,000 (0.78% increase). Based on the two effective results, the most efficient result to overcome the delays that occur is the addition of 4 workers.